2013
DOI: 10.4161/onci.23564
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of chimeric antigen receptor (CAR)-expressing T cells and host T cells for optimal elimination of established ovarian tumors

Abstract: Conditioning strategies that deplete host lymphocytes have been shown to enhance clinical responses to some adoptive T-cell therapies. However, host T cells are capable of eliminating tumor cells upon the relief of immunosuppression, indicating that lymphodepletion prior to T-cell transfer may reduce optimal tumor protection elicited by cell treatments that are capable of shaping host immunity. In this study, we show that adoptively transferred T cells bearing a chimeric antigen receptor (CAR) harness endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…148 CARs are limited in their ability to target only one antigen, making them more restricted than whole patient-derived TILs, however more recent data suggests that initial CAR T-cell activity may mobilize and activate endogenous CD4C and CD8C TILs to broaden the anti-tumor response in a mouse ovarian cancer model. 149 The cooperation of TILs with CAR T-cells, and the success of CAR T-cells in such preclinical models, shows promise for emerging immunotherapy trials.…”
Section: Additional Directions In Immunotherapymentioning
confidence: 99%
“…148 CARs are limited in their ability to target only one antigen, making them more restricted than whole patient-derived TILs, however more recent data suggests that initial CAR T-cell activity may mobilize and activate endogenous CD4C and CD8C TILs to broaden the anti-tumor response in a mouse ovarian cancer model. 149 The cooperation of TILs with CAR T-cells, and the success of CAR T-cells in such preclinical models, shows promise for emerging immunotherapy trials.…”
Section: Additional Directions In Immunotherapymentioning
confidence: 99%
“…Another candidate chemokine receptor that may be used to enhance ACT efficacy is CXCR3. An interesting study reported that adoptive transfer of T cells expressing a NKG2D-based CAR could recruit and activate endogenous antigen-specific CD4 þ and CD8 þ T cells at the tumor site in a CXCR3-dependent manner to achieve optimal eradication of ID8 ovarian cancer (54). Potential treatments such as PD-1 blockade (55) and chemotherapy (18) have been shown to enhance recruitment of adoptively transferred T cells to the tumor site by elevating the level of CXCR3 ligands.…”
Section: Adoptive T-cell Transfer and Traffickingmentioning
confidence: 99%
“…Studies of this approach in immune competent models are also planned, in light of the known immunomodulatory effects of carboplatin (42,43). In addition, recent data suggest that CARengineered T cells may enhance endogenous antitumor immunity against EOC, further emphasizing the need for such studies (44).…”
Section: Discussionmentioning
confidence: 99%